Endocrinopathies in Turkish Children with Thalassemia Major - Belma Haliloğlu; Gülen Tüysüz; Funda Tayfun (Journal of Pediatric Research, 2017)
Aim: Endocrinopathies are common in patients with thalassemia major (TM) and affect their life quality. Our aim was to identify the frequency of growth retardation and endocrine complications in these patients. Materials and Methods: Sixty-two patients aged 3-18 years with TM were evaluated retrospectively for height, weight, body mass index (BMI), and pubertal stage. Blood tests for endocrine function, and oral glucose tolerance test (OGTT) results were recorded. Results: The mean age of 62 subjects (33 females/29 males) was 10.4±3.9 years. The frequency of ≤-2 standard deviation scores was 37.1% for height, 33.9% for weight and 11.3% for BMI. Short stature, being underweight, and low BMI were significantly more prevalent in children over 7 years old (p<0.001). Delayed puberty/hypogonadism was present in 37% of 19 adolescents. Thirteen percent of the subjects had vitamin D deficiency (<10 ng/mL), hyperparathyroidism was observed in 29% of the subjects, while subclinical hypothyroidism (thyroid-stimulating hormone 5-10 IU/mL) was determined in 3 (5.5%) of the 55 subjects. In OGTT, impaired fasting glucose was seen in 7 subjects (14.5%), impaired glucose tolerance in 3 (6.3%), diabetes mellitus in 1 (2.1%), and hypoglycemia at 120-min was observed in 5 subjects (10.4%). Overall, 67.7% of the 62 subjects had height standard deviation score ≤-2 and/or at least one endocrinopathy. Conclusion: Growth retardation and endocrine problems are still a serious problem in TM patients, and develop particularly in those older than 7 years. Additionally, attention must be paid to hypoglycemia in these patients as well as diabetes.